Arterial Stiffness Preceding Diabetes: A Longitudinal Study. Issue 12 (4th December 2020) - Zheng, Mengyi; Zhang, Xinyuan; Chen, Shuohua; Song, Yongjian; Zhao, Quanhui; Gao, Xiang; Wu, Shouling
Abstract : Rationale: Previous studies on the relationship between diabetes and arterial stiffness were mostly cross-sectional. A few longitudinal studies focused on one single direction. Whether the association between arterial stiffness and diabetes is bidirectional remains unclear to date. Objective: To explore the temporal relationship between arterial stiffness and fasting blood glucose (FBG) status. Methods and Results: Included were 14 159 participants of the Kailuan study with assessment of brachial-ankle pulse wave velocity (baPWV) from 2010 to 2015, and free of diabetes, cardiovascular and cerebrovascular diseases, and chronic kidney disease at baseline. FBG and baPWV were repeatedly measured at baseline and follow-ups. Cox proportional hazard regression model was used to estimate hazard ratios and 95% confidence intervals (CIs) of incident diabetes across baseline baPWV groups: <1400 cm/s (ref), 1400⩽ baPWV <1800 cm/s, and ≥1800 cm/s. Path analysis was used to analyze the possible temporal causal relationship between baPWV and FBG, among 8956 participants with repeated assessment of baPWV and FBG twice in 2010 to 2017. The mean baseline age of the observed population was 48.3±12.0 years. During mean 3.72 years of follow-up, 979 incident diabetes cases were identified. After adjusting for potential confounders, the hazard ratio (95% CI) for risk of diabetes was 1.59 (1.34–1.88) for the borderline arterial stiffness group and 2.11 (1.71–2.61) for the elevated arterial stiffness group, compared with the normal ideal arterial stiffness group. In the path analysis, baseline baPWV was associated with follow-up FBG (the standard regression coefficient was 0.09 [95% CI, 0.05–0.10]). In contrast, the standard regression coefficient of baseline FBG for follow-up baPWV (β=0.00 [95% CI, −0.02 to 0.02]) was not significant. Conclusions: Arterial stiffness, as measured by baPWV, was associated with risk of developing diabetes. Arterial stiffness appeared to precede the increase in FBG. Abstract : Supplemental Digital Content is available in the text.